Coproduction inside the investment nexus; a retail investor perspective of demand and supply of responsible investment opportunities in South Africa - Roux, Andre (Graduate School of Business (GSB), 2023)
Little is known about responsible investment (RI) opportunities for retail investors in South Africa. Disconnect between RI demand and RI supply seems evident, undermining the growth of RI in this country, which in turn frustrates opportunities for economic growth and social well-being. “Over the past decade, environmental, social and governance (ESG) considerations have been among the most important factors responsible for shifting the axes of the financial industry”. This research examines retail investor demand for RI and supply of RI opportunities for the same market segment, in South Africa, observing inclusionary investment practice via the application of co-production. The paper reflects a survey of retail investor demand, from which 14 indicators are developed. The indicators are utilised to assess the dynamic between RI demand and available RI supply across three investment subsectors (commercial banks, asset managers, and alternative investment platforms). The paper leverages industry perspective to support its interpretations of existent demand for RI and accessible RI supply, circa 2019 to 2022. It intones the importance of using co-production to create investment context, to find equilibrium between supply and demand, and to enable resilient RI practice at the retail level. Methods of enabling inclusivity within nascent but pertinent RI practice for retail investors are reified. Deeper understanding of retail investor demand and methods of leveraging RI supply are required in future iterations of this type of research.